Satellite Image Transaction Service Improvement System Development and Implementation - Riyadi, Linggo Gagat; Riyanto, Indra; Susilo, Andi; Yasmiati, Yasmiati (LPPM of STIMIK ESQ, 2018)
PT Petacitra is a company that provides satellite data commercially. At present, the process is still done manually by email. To improve the satellite image transaction service, a web-based application is developed. The web-based process gives the marketing unit easier and more efficient transaction process. The method used in this research is System Development Life Cycle (SDLC) with waterfall modelling. The resulting system automates imagery ordering, preview upload, formulating the ofering proposal and generates the proposal template.